Porcine malignant hyperthermia during sevoflurane anaesthasia - KOSTOMITSOPOULOS (Ν.Γ. ΚΩΣΤΟΜΗΤΣΟΠΟΥΛΟΣ), N. G.; BALAFAS (Ε. ΜΠΑΛΑΦΑΣ), E.; MANGIARAS (Γ. ΜΑΝΤΖΙΑΡΑΣ), G.; PARONIS (Ε. ΠΑΡΩΝΗΣ), E.; ALEXAKOS (Π. ΑΛΕΞΑΚΟΣ), P.; KARAYANNAKOS (Π.Ε. ΚΑΡΑΓΙΑΝΝΑΚΟΣ), P. E. (Journal of the Hellenic Veterinary Medical Society, 2017)
During a surgical procedure, in a pig, under general anaesthesia with sevoflurane, the animal developed malignant hyperthermia. Malignant hyperthermia was expressed only by a progressive increase of rectal temperature without early symptoms from the cardiopulmonary system. The delayed onset of the malignant hyperthermia may be due to the co-administration of a number of drugs at the pre-anaesthetic phase as well as during the surgical procedure.